2015
DOI: 10.1002/tox.22183
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation of nuclear factor kappa B is regulated by G protein signaling pathway in arsenite-induced apoptosis in HBE cell line

Abstract: Arsenite is a certainly apoptosis inducer in various cell types. However, the detailed mechanism underlying how arsenite trigger apoptosis remains elusive. In this study, using human bronchial epithelial cell as a culture system, we demonstrated that arsenite-induced nuclear translocation of nuclear factor kappa B (NF-κB) resulted in the release of cytochrome c, the modulation of Fas and FasL, caspase activation, and ultimately leading to cell apoptosis. Importantly, we showed for the first time that the NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…(a,b,f)]. These results were consistent with our previous work and other studies showing that the activation of NF‐κB signaling pathway was involved in arsenite‐induced apoptosis (Druwe and Vaillancourt, ; Chen et al, ). Importantly, our results also showed that regulation of Ca 2+ homeostasis in ER by heparin or thapsigargin was able to affect the nuclear translocation of NF‐κB [Fig.…”
Section: Discussionsupporting
confidence: 92%
“…(a,b,f)]. These results were consistent with our previous work and other studies showing that the activation of NF‐κB signaling pathway was involved in arsenite‐induced apoptosis (Druwe and Vaillancourt, ; Chen et al, ). Importantly, our results also showed that regulation of Ca 2+ homeostasis in ER by heparin or thapsigargin was able to affect the nuclear translocation of NF‐κB [Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The apoptotic effects of aspirin on HT29 cells have been reported to be mediated by NFκB activation [ 30 ]. NFκB activation has also been shown to increase cell death induced by antimitotic agents [ 31 ] and different agents, including ascorbyl stearate and arsenite, have been shown to induce cell death in cervical and 16-HBE cells respectively [ 32 , 33 ]. It has also been reported that the pro- or anti-apoptotic function of NFκB has been determined by the nature of the stimulation [ 34 ] and collectively, even if NFκB is best characterized for its protective activity as a response to proapoptotic stimulation, it can also induce programmed cell death in certain circumstances [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has shown that cell viability of HBE cells treated by arsenite was markedly reduced (Chen et al, ). In this study, we further examined arsenite cytotoxicity of HBE cells with a new sensitive and nontoxic assay, the Alamar blue assay.…”
Section: Resultsmentioning
confidence: 99%